2019
DOI: 10.3390/geosciences9120507
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon-Isotope Record of the Sub-Seafloor Biosphere

Abstract: Sub-seafloor microbial environments exhibit large carbon-isotope fractionation effects as a result of microbial enzymatic reactions. Isotopically light, dissolved inorganic carbon (DIC) derived from organic carbon is commonly released into the interstitial water due to microbial dissimilatory processes prevailing in the sub-surface biosphere. Much stronger carbon-isotope fractionation occurs, however, during methanogenesis, whereby methane is depleted in 13C and, by mass balance, DIC is enriched in 13C, such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 113 publications
0
20
0
Order By: Relevance
“…Additionally, as discussed in the introduction, carbon isotope compositions between methane and CO 2 in marine sediments are commonly similar to values calculated based on theoretical estimates of equilibrium and, on this basis, it has been proposed that methane may form in or reach isotopic equilibrium with CO 2 in marine sediments (Bottinga, 1969;Yoshinaga et al, 2014;Meister and Reyes, 2019;Gropp et al, 2021).…”
Section: Comparison To Environmental Data and Microbial Culture Experimentsmentioning
confidence: 68%
See 1 more Smart Citation
“…Additionally, as discussed in the introduction, carbon isotope compositions between methane and CO 2 in marine sediments are commonly similar to values calculated based on theoretical estimates of equilibrium and, on this basis, it has been proposed that methane may form in or reach isotopic equilibrium with CO 2 in marine sediments (Bottinga, 1969;Yoshinaga et al, 2014;Meister and Reyes, 2019;Gropp et al, 2021).…”
Section: Comparison To Environmental Data and Microbial Culture Experimentsmentioning
confidence: 68%
“…Based on this, they suggested that methanogens in deep-sea sediments could promote CH 4 -CO 2 carbon isotopic equilibration during methane generation. Meister and Reyes (2019) further argued that methanogens can produce methane in carbon isotopic equilibrium with CO 2 because the carbon isotopic composition of methane formed by the reduction of CO 2 from the experiments of are similar to the values expected for equilibrium at the corresponding growth temperatures (35-85°C). Thus the problem has, over the past 50 years, come full circle, with the initial proposal that methanogens catalyze equilibration of carbon between methane vs. CO 2 in marine sediments, though initially dismissed, receiving renewed support.…”
Section: The Role Of Isotopic Equilibrium In Setting the Isotopic Composition Of Methanementioning
confidence: 88%
“…For the large variability of the C isotopes, explanations also include slow metabolisms that result in large fractionations, but also the pathway of methanogenesis. Methanogenesis occurring through the carbonate reduction pathway processes produces a 13 C-depleted methane and a strongly 13 C-rich residual CO 2 (Meister and Reyes, 2019). Calcite formed from the latter becomes isotopically heavy, particularly if there are very low concentrations of other C sources that can dilute the methane-related signature, which can explain the heavy δ 13 C values of > > +20‰ in these crystalline rock fractures (Drake et al, 2019).…”
Section: Isotopic and Biomarker Evidence And Timingmentioning
confidence: 99%
“…Various chemical compounds based on enriched ( 13 C) have a broad field of application [ 1 ]: Applications in medical fields: in clinical studies, differential diagnosis of multiple diseases, state of illness judgment, treatment evaluation, research on organ function and development of new drugs [ 2 ], such as PET diagnosis [ 3 ], 13 C-urea breath test [ 4 ], tumor therapy (boron neutron capture therapy) research on drugs [ 5 ], etc. ; Applications in life sciences fields: in the spectrum research of the structure and function of protein species by nuclear magnetic resonance (NMR) and mass spectrometer (MS), including isotope-coded affinity tag testing method (ICATTM), stable isotope labeled amino acid cell cultivation (SILAC), absolute quantification protein analysis method (AQUATM) [ 6 ]; Applications in energy metabolism: in sports medicine, child nutrition, food nutrition, weight loss and diet for astronaut using he-isotope tracing method [ 7 ]; Applications in agricultural scientific research fields: in the research of plant physiology and biochemistry, nutrition of soil and plant, plant protection, the improvement of rice, flower, agricultural products and other crops, nitrogen cycle of grassplot [ 8 ]; Applications in the research of environmental science: monitoring of ecosystem pollution, determining of the length of food chains, ascertaining the pollutant sources in air and water and defining the distribution area of plant [ 9 , 10 ]; Applications in analysis and testing: in the testing of food [ 11 ], pesticide residue analysis [ 12 ], drug and excitant, heroin testing [ 13 ], also in the research of geology, geochemistry, paleontology and ecology [ 14 , 15 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Applications in analysis and testing: in the testing of food [ 11 ], pesticide residue analysis [ 12 ], drug and excitant, heroin testing [ 13 ], also in the research of geology, geochemistry, paleontology and ecology [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%